The effects on nutrient digestibility of hay and silages made in different conditions in lambs - Seven, Pinar Tath; Çerçi, Ibrahim Halil (My University, 2006)
This study was conducted to determine the effects of silages and hay on feedlot performance and nutrient digestibility in lambs, and chemical differences in silages made in different media and forms. Twenty-four Akkaraman male lambs with an average mass of 27.93 kg and 8 months of age were used in the study. Lambs were assigned randomly to three groups. Barley-vetch (50/50%) was used as silo and for hay material two silos were installed. The control group was fed barley-vetch hay. Silo I was exposed to sunshine (group 1). Silo II was established in a long, closed hole which was open to air circulation and half underground (group II). Group III (control) consisted of barley-vetch hay. Dry matter levels were determined to be 33.20, 31.50 and 89.52% in group I-III, respectively. The pH, NH3-N and lactic acid levels of silages were observed to be 4.62 and 4.55; 0.54 and 0.50%; 2.35 and 2.50%, respectively. Dry matter intakes (DMI) of lambs were 941.44, 894.60 and 1119.00 g in groups I-III, respectively (P<0.05). Live mass gains (LWG) were 141.67, 145.83 and 122.92 g/day in group I-III, respectively. Feed conversion ratios were 6.67, 6.14 and 9.20 g DMI/g LWG in groups I-III, respectively. Dry matter, crude protein and crude fibre digestibility were determined to be 65.67, 67.99 and 59.78%; 61.40, 65.81 and 58.40%; 64.27, 66.06 and 59.67% in groups I-III, respectively (P<0.01).
Keywords: Digestibility; Ensile; Environment; Feedlot; Hay